The physics and technology basis entering European system code studies for DEMO. (11th October 2016) - Wenninger, R.; Kembleton, R.; Bachmann, C.; Biel, W.; Bolzonella, T.; Ciattaglia, S.; Cismondi, F.; Coleman, M.; Donné, A.J.H.; Eich, T.; Fable, E.; Federici, G.; et al.
Abstract: A large scale program to develop a conceptual design for a demonstration fusion power plant (DEMO) has been initiated in Europe. Central elements are the baseline design points, which are developed by system codes. The assessment of the credibility of these design points is often hampered by missing information. The main physics and technology content of the central European system codes have been published (Kovari et al 2014 Fusion Eng. Des . 89 3054–69, 2016 Fusion Eng. Des . 104 9–20, Reux et al 2015 Nucl. Fusion 55 073011). In addition, this publication discusses key input parameters for the pulsed and conservative design option EU DEMO1 2015 and provides justifications for the parameter choices. In this context several DEMO physics gaps are identified, which need to be addressed in the future to reduce the uncertainty in predicting the performance of the device. Also the sensitivities of net electric power and pulse duration to variations of the input parameters are investigated. The most extreme sensitivity is found for the elongation ( Δ κ 95 = 10 % corresponds to Δ P e l, n e t = 125 % ).